Analysis of Students’ Mathematical Communication Skills in Eight Grade of Junior high school on Number Patterns - Nailun Nikmah; Liknin Nugraheni (Journal of Education and Learning Mathematics Research (JELMaR), 2023)
In the past two years, scientific advancements have developed since the Coronavirus Disease of 2019. The Indonesian government has been forced to implement online learning activities led to several difficulties and hindered optimal learning experiences. This study aimed to analyze and describe the students’ low, moderate, and high mathematical communication skills on Number Patterns for Eighth graders of SMP Negeri 48 Surabaya, Academic Year 2022-2023. This study used descriptive qualitative research design. The data were collected using testing, interviews, and documentation. The results showed that students with high mathematical communication skills were able to demonstrate all indicators effectively. Students with moderate mathematical communication skills have achieved indicators related to expressing their understanding through mathematical concepts and graphical representations, but struggled to meet the indicator for creating mathematical models based on given problems. Students with low mathematical communication skills were able achieve indicators related to expressing their understanding through mathematical concepts, but failed to meet the indicators for expressing their understanding through graphical representations and creating mathematical models based on given problems. Based on the research findings, the authors suggest using an interactive learning model to improve students' mathematical communication skills, both written and oral. This model should actively involve students and address any knowledge gaps resulting from online learning.